2017
DOI: 10.2527/jas2017.1473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay on toxin binding capacity, ruminal fermentation, diet digestibility, and growth of steers fed high-concentrate diets1,2

Abstract: Three experiments were conducted to determine the effect of increasing concentrations of a smectite clay on toxin binding capacity, ruminal fermentation, diet digestibility, and growth of feedlot cattle. In Exp. 1, 72 Angus × Simmental steers were blocked by BW (395 ± 9.9 kg) and randomly allotted to 3 treatments (4 pens/treatment and 6 steers/pen) to determine the effects of increasing amounts of clay (0, 1, or 2%) on performance. The clay was top-dressed on an 80% concentrate diet at a rate of 0, 113, or 226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the studies of Maki et al (2016a) [34], and Maki et al (2016b) [35], a clear clay dose-dependent reduction of aflatoxin concentration was shown. Antonelo et al (2017) [33] proved a linear toxin dose effect, while Xiong et al (2015) [50] showed that the adsorbent at high AFB1 concentrations was not effective. Weatherly et al (2018) [44] found a quadratic decrease in AFB1 reduction by the adsorbent treatment in faeces.…”
Section: Adsorbents In Vitromentioning
confidence: 99%
“…In the studies of Maki et al (2016a) [34], and Maki et al (2016b) [35], a clear clay dose-dependent reduction of aflatoxin concentration was shown. Antonelo et al (2017) [33] proved a linear toxin dose effect, while Xiong et al (2015) [50] showed that the adsorbent at high AFB1 concentrations was not effective. Weatherly et al (2018) [44] found a quadratic decrease in AFB1 reduction by the adsorbent treatment in faeces.…”
Section: Adsorbents In Vitromentioning
confidence: 99%
“…Although this technique is simple and inexpensive when only a small number of animals are tested, it is labor intensive. Furthermore, this technique works well in a tiestall setting, where separate feed bunks can be allocated to each animal, but fails when animals are group housed with access to a communal bunk, where only a group average can be determined effectively (e.g., Silva Antonelo et al, 2017), can be used to roughly estimate feed intakes, although these are more suitable for management than for research or genetic selection.…”
Section: Determination Of As-fed Intakesmentioning
confidence: 99%